Suppression of ovulation and pharmacokinetics following subcutaneous administration of various doses of Depo-Provera®: a randomized trial - Vera Halpern; Rachael Fuchs; Vivian Brache; Luis Bahamondes; Maria Jose Miranda; Anja Lendvay; Leila Cochón; Douglas Taylor; Laneta J. Dorflinger (Elsevier, 2021)
Objectives: To identify the lowest dose of Depo-Provera that, when administered off-label subcutaneously, suppressed ovulation and had a pharmacokinetic profile consistent with a 4-month contraceptive effect.Study Design: We conducted a randomized, multicenter, parallel-group study to evaluate the pharmacokinetics (PK) and pharmacodynamics (PD) of medroxyprogesterone acetate (MPA) after subcutaneous injection of three different doses of Depo-Provera. We randomized sixty women between 18 and 40 years of age at low risk of pregnancy with confirmed ovulation and body mass index of 18 to 35 kg/m2 to receive a single injection of 45, 75 or 105 mg of Depo-Provera, or a single injection of Depo-subQ provera 104 as a reference drug (15 women per group) and followed them for 7.5 months. We evaluated suppression of ovulation as the primary outcome, and MPA concentrations, pharmacokinetic parameters, safety, and local tolerability as secondary outcomes.Results: Five women ovulated within four months of treatment initiation (three in the 45 mg group and two in the 75 mg group). MPA levels associated with ovulation were in general low, largely ≤ 0.2 ng/mL (the presumed contraceptive threshold). No women in either the 105 mg group or the Depo-subQ provera 104 group ovulated within four months. The PK parameters including Cmax, C119, and AUC0−119 for these 2 groups were similar but not equivalent.Conclusion: A dose of 105 mg of Depo-Provera injected subcutaneously was the lowest tested dose that consistently suppressed ovulation and maintained serum MPA levels consistent with contraceptive effect for at least 4 months. The PK and PD results for the 105 mg dose were similar to Depo-subQ provera 104 over this period.